2021
DOI: 10.1108/ssrp-05-2021-0011
|View full text |Cite
|
Sign up to set email alerts
|

Tensions with international mindedness: teaching in the international baccalaureate program

Abstract: PurposeInternational mindedness (IM) is a core element of International Baccalaureate (IB) programs. Implementation of IM varies with the type of international school and where the IB school is situated. This article seeks to understand the tensions that three teachers experienced while teaching the IB Diploma Program history curriculum.Design/methodology/approachFor this study, three IB teachers examined their experiences teaching the history curriculum. This article offers relevant research on the difficulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The global growth of the IBDP was evidenced in internal research (IBO, 2022b), Belal (2017) indicated that the IBDP in the Middle East has grown disproportionately and provided data to confirm her statement, while also noting that with regard to the Middle East ‘the research related to study of the outcomes of the IBDP’ was lacking (p 20). Ideally, IM is conceptually suited and therefore has a flexibility in applying and interpretating for the varied IBDP disciplines (Poonoosamy, 2016) to appeal to all regions, though this may be a double-edged sword as it is often left to the educator to implement (Chernoff, 2021). In addition, according to research arguing that IM remains foundational to the IBO and the IBDP (Belal, 2017), IM continues to conceptually evolve (Dickson et al, 2018; Gardner-McTaggart, 2016) and this challenges the ease of implementing (Wasner, 2016).…”
Section: Overview Findingsmentioning
confidence: 99%
“…The global growth of the IBDP was evidenced in internal research (IBO, 2022b), Belal (2017) indicated that the IBDP in the Middle East has grown disproportionately and provided data to confirm her statement, while also noting that with regard to the Middle East ‘the research related to study of the outcomes of the IBDP’ was lacking (p 20). Ideally, IM is conceptually suited and therefore has a flexibility in applying and interpretating for the varied IBDP disciplines (Poonoosamy, 2016) to appeal to all regions, though this may be a double-edged sword as it is often left to the educator to implement (Chernoff, 2021). In addition, according to research arguing that IM remains foundational to the IBO and the IBDP (Belal, 2017), IM continues to conceptually evolve (Dickson et al, 2018; Gardner-McTaggart, 2016) and this challenges the ease of implementing (Wasner, 2016).…”
Section: Overview Findingsmentioning
confidence: 99%